Designing Alternate Reality Games for effective learning: a methodology for implementing multimodal persistent gaming in university education. Issue 2 (3rd April 2021) - Tulloch, Rowan; Wolfenden, Helen; Sercombe, Howard
ABSTRACT: The Alternate Reality Game (ARG) is a relatively new form of gaming. Offering puzzles across a variety of media, ARGs require players to navigate digital and real worlds, form social connections, and demonstrate a wide variety of skills. This paper presents an Action Research approach to the use of ARGs in tertiary education contexts. Through two iterations of an Action Research cycle, the research identifies benefits in student engagement, attendance, attention to detail and connection with course materials. Through learning from the first cycle, a puzzle schema was developed for implementation in the second cycle. The first cycle also identified the need for a strong narrative structure for the game, and drew attention to a tension in the tradition of ontological ambiguity in ARGs: the 'this is not a game' fiction and the interpenetration of imaginary and real-world elements. Discarding this tradition in the second iteration, the research found significant advantages and no clear deficits in the clarification about the activity as a game. The research reaffirms the power of ARGs as a pedagogical tool, and offers a model of ARG implementation specifically designed for tertiary teaching environments.